Systematic review of severe fever with thrombocytopenia syndrome:virology, epidemiology, and clinical characteristics. (6th December 2013) - Liu, Shelan; Chai, Chengliang; Wang, Chengmin; Amer, Said; Lv, Huakun; He, Hongxuan; Sun, Jimin; Lin, Junfen
SUMMARY Severe fever with thrombocytopenia syndrome (SFTS) was firstly discovered in China in 2010, followed by several reports from many other countries worldwide. SFTS virus (SFTSV) has been identified as the causative agent of the disease and has been recognized as a public health threat. This novel Bunyavirus belongs to the Phlebovirus genus in the family Bunyaviridae. This review also describes the different aspects of virology, pathogenesis, epidemiology, and clinical symptoms on the basis of the published article surveillance data and phylogenetic analyses of viral sequences of large, medium, and small segments retrieved from database using mega 5.05, simplot 3.5.1, network 4.611, and epi information system 3.5.3 software. SFTS presents with fever, thrombocytopenia, leukocytopenia, and considerable changes in several serum biomarkers. The disease has 10 ~ 15% mortality rate, commonly because of multiorgan dysfunction. SFTSV is mainly reported in the rural areas of Central and North‐Eastern China, with seasonal occurrence from May to September, mainly targeting those of ≥50 years of age. A wide range of domesticated animals, including sheep, goats, cattle, pigs, dogs, and chickens have been proven seropositive for SFTSV. Ticks, especially Haemaphysalis longicornis, are suspected to be the potential vector, which have a broad animal host range in the world. More studies are needed to elucidate the vector–animal–human ecological cycle, the pathogenic mechanisms in high level animal models and vaccine development. © 2013 The Authors. Reviews in Medical Virology published by John Wiley & Sons, Ltd.